Design Parameters for Impact Research in Science Education - Jessaca Spybrook; Carl D. Westine; Joseph A. Taylor (SAGE Publishing, 2016)
The Common Guidelines for Education Research and Development were created as a joint effort between the Institute of Education Science and the National Science Foundation in an effort to streamline education research and contribute to an accumulation of knowledge that will lead to improved student outcomes. One type of research that emerged in the guidelines is impact research. In order to achieve the level of rigor expected for an impact study, it is common that a research team will employ a cluster randomized trial (CRT). This article provides empirical estimates of design parameters necessary for planning adequately powered CRTs focused on science achievement. Examples of how to use these parameters to improve the design of science impact studies are discussed.